Meet Felicity : an American girl : 1774 - Tripp, Valerie, 1951-; Andreasen, Dan (Middleton, WI : Pleasant Co., 1991)
In Williamsburg in 1774, nine-year-old Felicity rescues a beautiful horse who is being beaten and starved by her cruel owner.
"Book one"--P. [1] of cover.
"Ages 7 and up"--P. [4] of cover.
Keywords: Horses -- Fiction; Williamsburg (Va.) -- History -- Revolution, 1775-1783 -- Fiction